Mucous Membrane Pemphigoid, Bullous Pemphigoid, and Anti-programmed Death-1/ Programmed Death-Ligand 1: A Case Report of an Elderly Woman With Mucous Membrane Pemphigoid Developing After Pembrolizumab Therapy for Metastatic Melanoma and Review of the Literature - Zumelzu, Coralie; Alexandre, Marina; Le Roux, Christelle; Weber, Patricia; Guyot, Alexis; Levy, Annie; Aucouturier, Françoise; Mignot-Grootenboer, Sabine; Caux, Frédéric; Maubec, Eve; Prost-Squarcioni, Catherine (Frontiers in Medicine, 2018)
An 83-year-old patient developed erosions and a blister of the gingival mucous membrane, 6 months after discontinuation of the anti-programmed death-1 (anti PD-1) pembrolizumab therapy administered for 10 months for a metastatic melanoma. A diagnosis of mild mucous membrane pemphigoid (MMP) was made. Complete remission of MMP was rapidly obtained with minimal therapy (doxycycline). MMP remained in complete remission after a 3-month follow-up since discontinuation of the doxycycline therapy and no evidence of relapse of the melanoma was observed after a 14-month follow-up since discontinuation of the pembrolizumab therapy. The widespread use of anti PD-1 and anti-programmed death-ligand-1 (PD-L1) in several malignancies reveals new adverse events. MMP describes a group of chronic, inflammatory, mucous membrane-predominant, subepithelial auto-immmune blistering diseases. It shares similarities with bullous pemphigoid, another autoimmune blistering disease, but is clinically and immunologically distinct. Twenty-nine cases of bullous pemphigoid associated with anti PD-1/PD-L1 have been reported in the literature and one of MMP. Here, we described the case of a MMP developed after pembrolizumab and discussed the accountability of anti PD-1/PD-L1 in our case and the previous reported bullous pemphigoid and MMP cases using the Begaud system scoring.